2022
DOI: 10.1039/d2nj00285j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a series of high-energy and low-sensitivity composites with different desensitizers

Abstract: A series of ultrafine CL-20 and HMX energetic composites with different insensitive agents (DOS, PVAc and PVB) were prepared by electrostatic spray method. The results show that desensitizers have significant...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Subsequently, a large number of CL-20 cocrystals were successfully synthesized [ 5 ]. Through experimental tests and characterization of the material samples, it has been confirmed that the sensitivity of most CL-20 cocrystal energetic materials is significantly reduced and the safety is improved compared with CL-20 [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a large number of CL-20 cocrystals were successfully synthesized [ 5 ]. Through experimental tests and characterization of the material samples, it has been confirmed that the sensitivity of most CL-20 cocrystal energetic materials is significantly reduced and the safety is improved compared with CL-20 [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, research in energetic materials focuses on the development of modern energetic composites [ 1 ]. Through the progress of new high-energy and insensitive composites with elevated density, several issues have been addressed in recent years [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, research in energetic materials focuses on the development of modern energetic composites [ 1 ]. Through the progress of new high-energy and insensitive composites with elevated density, several issues have been addressed in recent years [ 1 , 2 ]. However, the most recently elaborated energetic formulations are still unable to substitute those actually employed in defense systems due to various drawbacks, such as incompatibility issues, poor thermal and physical stability, inappropriate energetic performance, and high cost, which restrict their further applications [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, the development of new insensitive and high-energy dense composites has addressed a series of challenges in the field of materials chemistry and advanced applications (e.g., high performance solid propellants and insensitive composite explosives) [ 1 , 2 ]. For instance, the most newly developed energetic materials, are still not able to completely replace currently used ones in the military systems due to several problems including chemical incompatibility, low thermal stability, worse sensitivity, as well as high cost, which impede their further use in military systems [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%